KAJIAN POTENSI PRODUKSI AKAR ADVENTIF PAKIS POHON Cyathea contaminans (CYATHEACEAE) DI JAWA BARAT DAN SUMATERA UTARA - Wardani, Wita (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Study on production potential of adventitious root of the scaly tree fern Cyathea contaminans was conducted in six locations in West Java and North Sumatra using 20 m x 50 m sampling plot. Data recorded in the study consisted of population density, individual heights and diameter, volume of adventitious roots and environmental factors. The highest population density was found in a population that consisted of saplings with the height of less than 2 m tall. While population with adult plants has the density of 26â36 individual/100 m2. The wighest average volume of adventitious root per individuals was found in a population that dominated by adult stands and lies on a gentle slope at 108,760.70 cm3/individuals, while the lowest was in a population that consisted of saplings. The result statistical analysis showed that production of adventitious root were significantly different in different habitat. Moreover, there was positive correlation between trunk diameter and individual height with the volume of adventitious root, and between the diameter with individual height.